Analysis of Loyalty and Quality of Service Against Patient Satisfaction of Social Security Agency of Health and General Patients in Neurology Polyclinic UOBK of Doctor Mohamad Saleh Regional Public Hospital, Probolinggo, East Java - Musdalifah, Illailatul; Indasah; Ellina, Agusta Dian (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Satisfaction of patients or insurance participants is one of the factors that can be used as a reference in determining the success of a service program. This means that the good quality of a service is not based on the service provider's perception, but based on the consumer's perception because it is the consumer who enjoys the services provided by the company. The study aimed to analyze the effect of loyalty and service quality on SCA patient satisfaction and general patients at the Neurology Polyclinic UOBK Dr. Mohamad Saleh Hospital, Probolinggo City. Subjects and Method: An observational study with a cross-sectional approach were conducted at Neurology Polyclinic UOBK Dr. Mohamad Saleh Hospital, Probolinggo, East Javaon August 2022. A total of 100 patients were selected for this study. The dependent variable was satisfaction. The independent variable were loyalty and service quality. The data were collected using a set of questionnaires and analyzed using linier regression. Results: Patient satisfaction increased with good loyalty (b= 2.26; p= 0.002), and good service quality (b= 2.03; p= 0.006). Conclussion: Patient satisfaction increased with good loyalty (b= 2.26; p= 0.002), and good service quality. Keywords: satisfaction, service quality, loyalty. Correspondence: Illailatul Musdalifah. Strada Institute of Health Sciences, Kediri, Indonesia. Jl. Manila No.37, Tosaren, Pesantren, Kediri, 64123 East Java. Email: yolacipit29@gmail.com. Mobile: 082332627340.